How Much Weight Loss is Required for Cardiovascular Benefits? Insights From a Metabolic Surgery Matched-cohort Study. Issue 4 (October 2020) - Aminian, Ali; Zajichek, Alexander; Tu, Chao; Wolski, Kathy E.; Brethauer, Stacy A.; Schauer, Philip R.; Kattan, Michael W.; Nissen, Steven E.
Abstract : Objective: The aim of this study was to determine the minimum amount of weight loss required to see a reduction in major adverse cardiovascular events (MACE). Background: Although obesity is an established risk factor for morbidity and mortality, the minimum amount of weight loss to have a meaningful impact on cardiovascular health and survival is unknown. Methods: Patients with obesity (body mass index ≥30 kg/m 2 ) and type 2 diabetes who underwent metabolic surgery in an academic center (1998–2017) were propensity-matched 1:5 to nonsurgical patients who received usual care. The adjusted linear and nonlinear effects of weight loss (achieved in the first 18 months after the index date) were studied to identify cut-offs for the minimum weight loss to achieve decreased risk of all-cause mortality and MACE (composite of all-cause mortality, coronary artery events, cerebrovascular events, heart failure, nephropathy, and atrial fibrillation). Results: A total of 7201 patients (1223 surgical and 5978 nonsurgical) with a median follow-up time of 4.9 years (interquartile range, 3.5–7) were included. The positive effect of metabolic surgery was still present after adjusting for weight loss amounts, suggesting that there are weight loss-independent factors contributing to a reduction in risk of MACE and all-cause mortality in the surgical cohort. After considering the weighted estimates from a diverse set of models, the risk of MACE decreases after approximately 10% of weight is lost in the surgical group and approximately 20% in the nonsurgical group. For all-cause mortality, the threshold for benefit appeared to be approximately 5% weight loss after metabolic surgery and 20% in the nonsurgical group. Conclusions: This large matched-cohort study identified the minimum weight loss thresholds for reduction in risk of MACE and all-cause mortality in patients with obesity and diabetes. Furthermore, in our analysis, the effect of surgery was still present after accounting for weight loss, which may suggest the presence of weight-independent beneficial effects of metabolic surgery on MACE and survival. Abstract : Supplemental Digital Content is available in the text